Brief cognitive behavioral therapy for chronic insomnia in a primary care setting: a case report - Dellma Anggini; Mualimin (Published by Universitas Gadjah Mada, 2026)
Chronic insomnia with anxiety disorders is a common non-specialist mental health condition frequently encountered in primary care. Although the WHO Mental Health Gap Action Programme (mhGAP) recommends psychosocial interventions at this level, skepticism persists regarding the feasibility of implementing brief psychotherapy within the high-volume workflow of Indonesian community health centers. This case report aims to illustrate the clinical application and operational feasibility of Brief Cognitive Behavioral Therapy (BCBT) in a primary health center setting. We report a 40-year-old female with chronic insomnia accompanied by somatic symptoms, including palpitations and tachycardia, without underlying medical comorbidities. The patient exhibited significant cognitive distortion in the form of sleep state misperception. As the primary treatment modality, a four-session BCBT intervention was conducted every two weeks (30–45 minutes per session). The curriculum included autonomic, behavioral, and cognitive (ABC) model psychoeducation, cognitive restructuring, scheduled worry period, behavioral activation, relaxation, lifestyle modification, and relapse prevention. Evaluation was performed using the insomnia severity index (ISI), subjective units of distress scale (SUDS), and collaborative patient-reported outcome measures (PROM) encompassing three domains: sleep duration, frequency, and anxiety levels. The collaborative goal setting (CGS) of at least 5 hours of sleep, 5 days a week without anxiety, was fully achieved by the third session and remained stable until thereafter. This case illustrates that structured psychotherapy such as BCBT is potentially feasible within a busy PHC workflow, provided there is institutional commitment from facility leadership, a dedicated psychotherapy schedule for trained mental health providers at least once a week, and functional early detection within general outpatient services. While these results are promising for this individual case, further studies are needed to evaluate the scalability and standardized implementation of this model across diverse primary care settings in Indonesia.